Association of physical activity with arterial stiffness and pulsatility in a community-based cohort - Mawra Jha; Zhiyong Dong; Sean Meagher; Nicole L Spartano; Emelia J Benjamin; Ramachandran S Vasan; Gary F Mitchell; Connie W Tsao (Vascular Medicine, 2026)
Introduction: Central arterial stiffness and pressure pulsatility are key measures of arterial health and cardiovascular disease (CVD). Acute physical activity (PA) improves vascular function; however, its relationship with arterial health across varying habitual PA levels remains understudied. Methods: We analyzed Framingham Heart Study (FHS) data (Generation 2: Exam 8, 2005–2008, n = 2999 and Generation 3: Exam 1, 2002–2005, n = 4064). Habitual PA was assessed using a standardized questionnaire. Carotid-femoral pulse wave velocity (niCFPWV, inverse-transformed CFPWV), central pulse pressure (CPP), and forward wave pressure (FWP) were measured using applanation tonometry. We examined associations between PA scores (as quintiles) and arterial health using linear regression and effect modification by age and sex, as well as mediation by arterial health measures on heart failure, CVD mortality, and all-cause mortality. Results: In 6451 FHS participants (mean age 50 ± 15 years, 55% women), the highest quintile of PA was associated with lower aortic stiffness (niCFPWV, β = −0.06 ± 0.02, p = 0.01). Continuous PA was associated with higher CPP (std β = 0.02 ± 0.01, p = 0.03) but not FWP. We observed an age-interaction: PA was associated with lower niCFPWV in individuals ⩾ 48 years (std β = −0.21 ± 0.07, p = 0.005) and higher CPP in those < 48 years (std β = 0.01 ± 0.004, p = 0.01). No significant effect modification by sex was noted. In stratified analyses, PA was associated with higher CPP among individuals without hypertension (β = 0.02 ± 0.01, p = 0.02), but not among those with hypertension. In mediation analyses, vascular measures did not contribute significantly to cardiovascular outcomes. Conclusion: Higher PA score was associated with lower arterial stiffness, particularly in older adults, and with higher pressure pulsatility in younger adults.